2022
DOI: 10.1101/2022.02.10.479831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformational switch in the alpha-synuclein C-terminus domain directs its fibril polymorphs

Abstract: α-Synuclein inclusion bodies are a pathological hallmark of several neurodegenerative diseases. Although it has been hypothesized a relationship between fibril polymorphism and different pathologies, the molecular origins of polymorphism are not understood. Here, employing biophysical approaches, we demonstrate that the conformational state of the monomeric αSyn is responsible for fibril polymorphism: αSyn can exist as a compact monomer that produces rod fibrils, and as extended monomers that generate twisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 92 publications
2
4
0
Order By: Relevance
“…The rod seeds predominantly have two parallel protofilaments, while the twist seeds comprise two intertwined protofilaments. These morphologies are consistent with those reported. ,, Both types of seeds have an equivalent average length of around 50 nm. From Figure B, we can clearly see the formation of the fibril network composed of dense fibrils on the QCM surfaces, on which these seeds were immobilized by flowing the monomer solution.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The rod seeds predominantly have two parallel protofilaments, while the twist seeds comprise two intertwined protofilaments. These morphologies are consistent with those reported. ,, Both types of seeds have an equivalent average length of around 50 nm. From Figure B, we can clearly see the formation of the fibril network composed of dense fibrils on the QCM surfaces, on which these seeds were immobilized by flowing the monomer solution.…”
Section: Resultssupporting
confidence: 92%
“…To further investigate the relationship between the fibril morphology and the network stiffness, we monitored the α-syn aggregation reaction using the wireless QCM at a higher NaCl concentration of 500 mM. At this salt concentration, elongated fibrils show different morphologies due to the conformation change of α-syn monomer as has been reported in our recent study, which is also confirmed in bulk solutions as shown in Figure S2: In the early stage of the seeding reaction, there is no remarkable difference in the seeding reaction between with rod and twist seeds at the low NaCl concentration (Figure S2A), but the seeding reaction with rod seeds proceeds faster than that with twist seeds at the high NaCl concentration (Figure S2B).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Instead of performing clustering analysis using global features as shown in Figure 3 , we can extend these ideas to include local features. Due to the complex nature of the problem, in many cases information about which residues/regions of the protein are important/irrelevant for misfolding/aggregation is sparse ( Aguirre et al, 2022 ; Seetaloo et al, 2022 ). Perhaps the most informative results come from mutational studies that assess the effect of mutations on misfolding/aggregation rate in a rigorous way.…”
Section: Extracting Information About Misfolding/aggregation Sub-ense...mentioning
confidence: 99%